Using Information Technology Security to Protect the Network Models (مجلة المنصور, 2023)
This paper discuss how to use the principles of information technology security with models , the principles of information security : confidentiality , integrity , availability, accountability, and assurance are used to protection of information systems against unauthorized access to or modification of information, whether in storage , processing or transit, and against the denial of service to authorized users or provision of service to authorized users, including those measures necessary to detects , document and counter such threats .This paper present how can implement the principles of information technology security on the Network Model (Intranet models ) and we make the analysis the result and conclude this principles is very important to increase the protection of models in net.